(untitled) (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Spasmodic dysphonia (SD) is a focal dystonia and adductor SD is the commonest form. The standard treatment for adductor SD is EMG-guided, transcutaneous injections of botulinum toxin into the thyroarytenoid muscle. Methods: This is a prospective study on patients with adductor spasmodic dysphonia done in Bangladesh Medical University, Dhaka from January 2020 to January 2023. All of the patients were studied with a complete head and neck and neurologic examination, fiberoptic laryngostroboscopy, and a speech evaluation including the Universal spasmodic dysphonia rating scale and VHI. Proper counselling regarding the results & possible complication was done. All patients received botulinum toxin injections into the thyroarytenoid muscles under fiberoptic laryngostroboscopy guidance, post injections following results were recorded. Results: The median duration of symptoms prior to diagnosis was 12 months: all were adductor in type. The average age at onset was 44 years. The time for botulinum toxin to take effect averaged 3 days (peak effect, 7 days). The patients received substantial relief from their SD symptoms, an average functional improvement of 40%. Patients’ best voice was achieved within one week and persisted for an average of 14 weeks. Side effects from the injections included mild breathiness (68%) and mild choking onfluid (56%). After injection, decreased potential for volume was a common complaint. Almost all of the patients returned for repeat injections when the benefit diminished (After 12-16 weeks). Conclusion: Botulinum toxin therapy has become the standard care for the treatment of SD. An acceptable and flexible treatment plan to produce a balance between decreased spasms and loss of function must be developed for each patient. Bangladesh J Otorhinolaryngol 2025; 31(2): 52-61